Proceedings of IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.1996.503848
|View full text |Cite
|
Sign up to set email alerts
|

The noise amplification index for optimal pose selection in robot calibration

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 11 publications
0
71
0
Order By: Relevance
“…(12) M is called the information matrix, moment matrix, or covariance matrix in different literatures. The minimization of a matrix has many expressions corresponding to different physical meanings.…”
Section: A Parameter Estimation Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) M is called the information matrix, moment matrix, or covariance matrix in different literatures. The minimization of a matrix has many expressions corresponding to different physical meanings.…”
Section: A Parameter Estimation Optimizationmentioning
confidence: 99%
“…The minimum singular value uses the worst observability of the parameter error as the criterion. Nahvi and Hollerbach [12] also proposed as an observability index the square of smallest non-zero singular value divided by the largest singular value of X, called the noise amplification index and referred to here as O 4 . Nahvi and Hollerbach [12] compared different observability indexes, and found that O 1 was worse than the others.…”
Section: Introductionmentioning
confidence: 99%
“…However perfect measurements do not exist and is necessary to choose best calibration poses. There exist approaches [4,32], where a noise amplification index is used to identify poses in which errors in the parameters of the robot are especially critical; this is given when a calibration pose is near from a singularity or from workspace boundaries. However in a practical calibration process, if poses are extremely near of singularities, those poses are able to produce unpredictable movements (due to kinematic errors).…”
Section: A Selection Of Calibration Posesmentioning
confidence: 99%
“…where λ min and λ max are the smallest and largest eigenvalues of K. The NAI was described by Nahvi and Hollerbach [8], and Simon [12] found that are there were four important problems that must be addressed when using the NAI as a criterion for point selection.…”
Section: Strategies For Registration Point Selectionmentioning
confidence: 99%